A rare case of hemodialysis-related portosystemic encephalopathy and review of the literature. Issue 4 (3rd July 2020) - Geerinckx, Barbara; Hellemans, Rachel; Van Craenenbroeck, Amaryllis H.; Francque, Sven; De Waele, Liesbeth; Kerstens, Jeroen; Van Gaal, Pieter-Jan; Bracke, Bart; Michielsen, Peter; Vanwolleghem, Thomas
ABSTRACT: Hemodialysis-related portosystemic encephalopathy (HRPSE) is a clinical phenomenon where portosystemic encephalopathy (PSE) develops without liver dysfunction, usually caused by changes in the portosystemic blood flow related to hemodialysis. We describe the case of a 22-year old patient with a transjugular intrahepatic portosystemic shunt (TIPS) who developed HRPSE several months after initiation of hemodialysis. Despite initial therapy with laxatives and neomycin symptoms recurred. It was only after relocation of the hemodialysis catheter from the superior caval vein to the femoral vein that symptoms completely resolved.